ADCP data from lander deployment BoBo1 during SONNE cruise SO242/1 nearby the DISCOL area - Jens Greinert (PANGAEA, 2018)
BoBo lander from NIOZ (Bottom Boundary) was deployed in the undisturbed area three miles south of the DISCOL Experimental Area (DEA) for a duration of 5 days (2015-07-30 to 2015-08-05). This dataset contains raw and processed data from 300kHz upward looking ADCP and 1200kHz downward looking ADCP.